2022
DOI: 10.4314/ijbcs.v15i5.38
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation de la contamination des éléments traces métalliques dans les sédiments de la rivière N’zi, Côte d’Ivoire

Abstract: Les éléments traces métalliques s’accumulent dans les systèmes aquatiques et peuvent dégrader la qualité des eaux et présenter une menace pour la santé humaine et la faune. Cependant peu d’étude existe sur la concentration totale des métaux dans les cours d’eau ivoiriens impactées par les activités agricoles. Pour contribuer à la mise en place d’une base de données, nous avons étudié la distribution et le niveau de contamination du Cu, Hg, Pb, Ni et Zn dans les eaux et les sédiments de la rivière N’zi. La conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
(13 reference statements)
2
1
1
Order By: Relevance
“…The results obtained by Muhammad in the sediments of Weihe River (China) show contamination [36]. The results obtained in this study are clearly weaker than those obtained by Ouattara in the N'zi River in Côte d'Ivoire [36].…”
Section: Contamination Factor (Cf) and Average Contamination Index (I...contrasting
confidence: 84%
See 2 more Smart Citations
“…The results obtained by Muhammad in the sediments of Weihe River (China) show contamination [36]. The results obtained in this study are clearly weaker than those obtained by Ouattara in the N'zi River in Côte d'Ivoire [36].…”
Section: Contamination Factor (Cf) and Average Contamination Index (I...contrasting
confidence: 84%
“…Similarly, the results obtained by Banu et al, (2013) [35] are much higher than our results (28.30 -36.4 mg/kg) and also those recorded by Rabee et al, (2011) (8 -59 µg/g) [27]. The values obtained by Muhammad et al, (2020) [36] in Weihe River in China are much higher. For Cr VI, the concentrations vary from 0.02 mg/kg to 0.04 mg/kg in S1 (low water in June) for a mean of 0.031 ± 0.009 µg/kg.…”
Section: Heavy Metal Content In Sedimentssupporting
confidence: 75%
See 1 more Smart Citation
“…In the country and in the sub-region, authors have also identified heavy metals in sediments. These include scientific works [23] [31] [32] [33], which found a range of heavy metals in sediments from the Gogounou, Kandi and Banikoara cotton belts in Benin, the Weija water reserve in Ghana, the lake at the Nangbéto hydroelectric dam in Togo and sediments from the N'zi river in Côte d'Ivoire. Lead concentrations were highest at all the stations, with the highest concentration of 265.96 ± 21.02 mg/Kg recorded at the Aguigadji station during the rainy season.…”
Section: Ecological Risk Index (Ri) Valuesmentioning
confidence: 99%
“…In rural areas, agricultural activities, through the massive use of fertilizers and pesticides, represent the main sources of contamination of trace metal elements in aquatic environments [6][7][8].…”
Section: Introductionmentioning
confidence: 99%